2014
DOI: 10.1155/2014/674583
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic Thyroid Cancer: The Addition of Systemic Chemotherapy to Radiotherapy Led to an Observed Improvement in Survival—A Single Centre Experience and Review of the Literature

Abstract: Introduction. Anaplastic thyroid carcinoma (ATC) is rare yet accounts for up to 50% of all thyroid cancer deaths. This study reviews outcomes of patients with confirmed ATC referred to a tertiary oncology centre plus reviews the literature to explore how poor outcomes may be improved. Materials and Methods. The management and outcomes of 20 patients with ATC were reviewed. Results. Median age at diagnosis was 69.5 years. 19 patients died due to ATC, 40% of whom died from asphyxiation. Median survival for all c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 45 publications
1
16
0
1
Order By: Relevance
“…Although most of the series demonstrated female predominance 1, 4, 22 , our study reflected more male patients similar to reports by Lowe et al 28 and Remick et al 29 which documented high male to female patients' ratio. Female gender was identified by Roche et al as a poor prognostic factor 30 .…”
Section: Discussionsupporting
confidence: 89%
“…Although most of the series demonstrated female predominance 1, 4, 22 , our study reflected more male patients similar to reports by Lowe et al 28 and Remick et al 29 which documented high male to female patients' ratio. Female gender was identified by Roche et al as a poor prognostic factor 30 .…”
Section: Discussionsupporting
confidence: 89%
“…Tallroth et al [4] reported that 41 (60%) of 68 patients during the period from 1930 to 1970 died from asphyxiation, and Lowe et al [5] reported that 8 (40%) of 20 patients died from asphyxiation. A total of 113 (21%) of 547 patients in the study by Sugitani et al [6] and 6 (18%) of the 33 patients in our study died from local recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The median survival and the 1-year overall survival (OS) rate have been re-ported to be 5 months and 20%, respectively [3]. The most common causes of death have been reported to be primary tumor growth, asphyxiation, or active bleeding from the neck [4,5]. Sugitani et al [6] showed by multivariate analysis that surgery and external beam radiotherapy ≥40 Gy were predictors of significantly better OS for patients with any stage of ATC and that chemotherapy was a predictor of significantly better OS for patients with stage IVB or IVC.…”
Section: Introductionmentioning
confidence: 99%
“…Patients receiving radiotherapy and chemotherapy had significant longer OS (n = 3, median 220 days) compared to patients with surgery and radiotherapy (n = 4, median OS 176 days) and patients receiving only radiotherapy (n = 6, median OS 58.5 days). However, no multivariate analysis is provided and the study suffers from its limited number of patients (Lowe et al 2014). …”
Section: Radiotherapymentioning
confidence: 99%